Clinical applications of microperimetry in RPGR-related retinitis pigmentosa: a review - Buckley, TMW; Jolly, JK; Josan, AS; Wood, LJ; Cehajic-Kapetanovic, J; MacLaren, RE (Wiley, 2021)
Microperimetry, or fundus-tracked perimetry, is a precise static-automated perimetric technique to assess central retinal function. As visual acuity only deteriorates at a late disease stage in RPGR-related retinitis pigmentosa (RP), alternative markers for disease progression are of great utility. Microperimetry assessment has been of critical value as an outcome measure in a recently reported phase I/II gene therapy trial for RPGR-related RP, both in terms of detecting safety and efficacy signals. Here, we performed a review of the literature. We describe the principles of microperimetry before outlining specific parameters that may be useful as outcome measures in clinical trial settings. The current state of structure-function correlations between short-wavelength autofluorescence, optical coherence tomography and adaptive optics in RPGR-related retinitis pigmentosa are also summarized.